Evaluation of genetic trend in milk production of buffalo cattle in Colombia - Divier Antonio Agudelo-Gómez; Sebastián Pineda-Sierra; Diana Solano; Andrés Felipe Pérez-Rojo; Edison Julián Ramírez-Toro (Revista Científica)
Assessing genetic trends in livestock is pivotal for comprehending how populations have evolved over time. This provides valuable insights into the direction and magnitude of genetic change, which is crucial for evaluating the outcomes of selection processes within herds. This study aimed to evaluate the genetic trend in milk production of buffalo cattle in Colombia. The study used the productive database of purebred Murrah Buffaloes recorded by the Colombian Buffalo Breeders Association (ACB), encompassing productive and genealogical records of 774 animals born between 2008 and 2017. A GAMS model was applied to assess genetic values, considering the birth year of the animal. The mean genetic value in the evaluated population was 45.42 ± 85.31 kg, with minimum and maximum values of -160.54 and 377.34 kg, respectively. When analyzing genetic values by year, the highest value was observed in 2014 (56.26 kg), while the lowest was recorded in 2017 (32.65 kg). The GAMS model estimated an intercept of 45.42 kg (p<0.001), with an explained variance of 63%. The genetic trend showed stable values from 2008 to 2011, but from that point onwards, a decline was evident, becoming more pronounced from 2014 onward. The results indicate a decrease in genetic values for the milk production trait in the evaluated population. This decrease is attributed to the limited use of high-genetic-value sires in biotechnological programs and low selection intensity. To achieve favorable genetic progress, it is important to conduct selection processes based on genetic evaluations undertaken in the country, increase selection intensity by the widespread use of sires with positive genetic values, and restrict the use of animals with negative genetic values. In 2015, Agudelo et al. also estimated similar genetic trends without significant increases in the genetic trend for milk production. Strategies should be developed to allow the introduction of new animals or genetic lines through the purchase or exchange of sires with positive genetic values. Those strategies can enhance genetic diversity and provide new opportunities for improvement by expanding the range of selection possibilities. Additionally, the use of biotechnological tools such as artificial insemination and embryo transfer should be promoted to expedite the dissemination of genetically superior animals.